2008
DOI: 10.1143/jjap.47.6574
|View full text |Cite
|
Sign up to set email alerts
|

Water Purification Using the Adsorption Characteristics of Microbubbles

Abstract: Recently, technology using microbubbles has been studied for water purification. However, the mechanism and physical parameters of the purification process have not yet been sufficiently clarified. The purpose of this study is to clarify the physical parameters of microbubbles that influence water purification. Firstly, we measured and analyzed the purifying performance using various millimeter-sized bubbles, and we obtained the equilibrium constant of the pollutant adsorbed on the bubble surface from the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…Microbubbles with 30 lm radius were first found by Turner (1961) in water and they were found to exist for long periods of time, contradictory to classical theory. The significant factor determining water purification effectiveness of MNB technology is the surface area, which relates to the pollutant adsorption on the bubble surface (Yoshida et al, 2008). Micro-nano bubbles are found to be negatively charged under a wide range of pH conditions (Takahashi, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Microbubbles with 30 lm radius were first found by Turner (1961) in water and they were found to exist for long periods of time, contradictory to classical theory. The significant factor determining water purification effectiveness of MNB technology is the surface area, which relates to the pollutant adsorption on the bubble surface (Yoshida et al, 2008). Micro-nano bubbles are found to be negatively charged under a wide range of pH conditions (Takahashi, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism induces intense turbulent pressure fluctuations leading to bubble breakup, as opposing to the bubble internal pressure and surface tension. An additional effect in Venturi MBGs is the saturated-vapour pressure in the divergent section, which can result in cavitation [21].…”
Section: Introductionmentioning
confidence: 99%
“…The Venturi-type bubble generator is similar to the pressurized dissolution type in the bubble generation method and has been widely used due to its simple structure. Yoshida et al [8] found that microbubbles were generated through the collision of a gas with the pressure wall formed by a shock wave. Yin et al [9] conducted an experimental study on the bubble size distribution in the turbulence flow for the Venturi-type bubble generator and proved that the averaged bubble diameter has a dependence on the Reynolds number.…”
Section: Introductionmentioning
confidence: 99%